Penggunaan Sistem Arduino Untuk Switch Control Lampu Dan Listrik Dengan Smartphone - Syahri Ramadhan; Anjar Wanto; Indra Gunawan (STMIK Budi Darma, 2021)
The development of technology and lifestyle now shows the increasing importance of practicality and efficiency cause the need to control various electrical loads is not only done by requiring that in close proximity these electrical devices and pressing the on / off switch but can also be done remotely (Android). There is various ways to control the electrical load. Controlling electrical loads that are often encountered, namely by push the on / off switch. As time goes by it develops as an alternative in controlling electrical loads, among others, by touching a sensor to control the electricity load on / off, then there is more Electricity load control by using Android to control on / off electricity load. With the background above, then I want to make an electronic circuit that is capable of being able to control the lights using Android using the BLYNK app. Requirements that must exist to build This application is an Android, Relay v5, ATMega 328p microcontroller, and several other devices.